Cytarabine dose reduction in patients with low‐risk acute myeloid leukemia: A report from the Children's Oncology Group. Issue 1 (2nd September 2021) - Getz, Kelly D.; Alonzo, Todd A.; Sung, Lillian; Meshinchi, Soheil; Gerbing, Robert B.; Raimondi, Susana; Hirsch, Betsy; Loken, Michael; Brodersen, Lisa Eidenschink; Kahwash, Samir; Choi, John; Kolb, E. Anders; et al.
Abstract: Background: The optimal number of chemotherapy courses for low‐risk (LR) pediatric acute myeloid leukemia (AML) is not known. Objective: To compare outcomes for four (21.6 g/m 2 cytarabine) versus five (45.6 g/m 2 cytarabine) chemotherapy courses for LR‐AML using data from Children's Oncology Group (COG) AAML0531 and AAML1031. Methods: We compared relapse risk (RR), disease‐free survival (DFS), and overall survival (OS), and the differential impact in LR subgroups for patients receiving four versus five chemotherapy courses. Cox (OS and DFS) and risk (RR) regressions were used to estimate hazard ratios (HR) to compare outcomes. Results: A total of 923 LR‐AML patients were included; 21% received five courses. Overall, LR‐AML patients who received four courses had higher RR (40.9% vs. 31.4%; HR = 1.40, 95% confidence interval [CI]: 1.06–1.85), and worse DFS (56.0% vs. 67.0%; HR = 1.45, 95% CI: 1.10–1.91). There was a similar decrement in OS though it was not statistically significant (77.0% vs. 83.5%; HR = 1.45, 95% CI: 0.97–2.17). Stratified analyses revealed the detrimental effects of cytarabine dose de‐escalation to be most pronounced in the LR‐AML subgroup with uninformative cytogenetic/molecular features who were minimal residual disease (MRD) negative after the first induction course (EOI1). The absolute decrease in DFS with four courses for patients with favorable cytogenetic/molecular features and positive MRD was similar to that observed for patients with uninformative cytogenetic/molecular features and negative MRD at EOI1, though not statistically significant. Conclusions: Our results support de‐escalation of cytarabine exposure through the elimination of a fifth chemotherapy course only for LR‐AML patients who have both favorable cytogenetic/molecular features and negative MRD after the first induction cycle.